1990
DOI: 10.1093/ije/19.3.621
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory History during Infancy and Childhood, and Respiratory Conditions in Adulthood

Abstract: The aim of this paper was to study respiratory disorders in infancy and childhood as a risk factor for respiratory conditions in adulthood. During the first part of the survey 15,247 adolescents in the Bordeaux area (average age: 16.5 years, boys = 46.6%) filled in a self-administered questionnaire concerning their respiratory history during infancy and childhood, their present symptoms and their smoking habits. Each subject with chronic cough (n = 538) was then matched with two controls (n = 1094) and the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Although many groups have reported an association between lower respiratory infections in childhood and later respiratory morbidity, 12,15,16 this is the first case-control study of childhood pneumonia and radiologically proved bronchiectasis. The most striking observation in this study is the strong and significant association between hospitalized pneumonia and bronchiectasis, in particular recurrent (Ͼ1) hospitalized pneumonia and more severe pneumonia episodes with longer hospital stay and requirement for oxygen.…”
Section: Discussionmentioning
confidence: 81%
“…Although many groups have reported an association between lower respiratory infections in childhood and later respiratory morbidity, 12,15,16 this is the first case-control study of childhood pneumonia and radiologically proved bronchiectasis. The most striking observation in this study is the strong and significant association between hospitalized pneumonia and bronchiectasis, in particular recurrent (Ͼ1) hospitalized pneumonia and more severe pneumonia episodes with longer hospital stay and requirement for oxygen.…”
Section: Discussionmentioning
confidence: 81%
“…Respiratory illness in childhood is a risk factor for chronic respiratory morbidity and pulmonary dysfunction in adulthood. 1,2 The burden of respiratory illness, the second highest cause of death in adult indigenous males and females, and the commonest cause of hospitalization in children under 5 years in the Northern Territory, 3 remains high in indigenous Australians. 4 In most affluent countries, childhood bronchiectasis not related to underlying causes such as cystic fibrosis (CF), ciliary dyskinesia, immune deficiency, or focal lung abnormalities has largely disappeared in mainstream communities.…”
Section: Introductionmentioning
confidence: 99%
“…Since Reid and others drew attention to the presumptive link between childhood lower respiratory tract illness and later adult chronic bronchitis1-3 many studies have shown the association of early life lower respiratory illness with later increased risk of lower respiratory problems in childhood,>7 in adolescence or young adult life,"' and in older adults.' [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Migrant studies offer some confirmation of the childhood risks. '5 Evidence for the risk of lower respiratory illness during childhood from poor social and home circumstances, 16-19 parental smoking, 20-22 and exposure to high levels of atmospheric smoke pollution7-9 17 23 iS strong.…”
mentioning
confidence: 99%